2006
DOI: 10.1073/pnas.0607242103
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a pathogenic antibody response to native myelin oligodendrocyte glycoprotein in multiple sclerosis

Abstract: Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system. Although the cause of MS is still uncertain, many findings point toward an ongoing autoimmune response to myelin antigens. Because of its location on the outer surface of the myelin sheath and its pathogenicity in the experimental autoimmune encephalomyelitis model, myelin oligodendrocyte glycoprotein (MOG) is one of the potential disease-causing self antigens in MS. However, the role of MOG in the pathogenesis of MS has r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
194
3
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 219 publications
(205 citation statements)
references
References 40 publications
3
194
3
5
Order By: Relevance
“…In the CSF, antigen microarrays in MS have detected antibodies to lipid (6) and ␣B-crystallin (23) and of note, the ␣B-crystallin reactive antibodies were of low affinity, detectable at 1:20 dilution (23). High-affinity autoreactive antibodies in the serum have not been consistently found in MS (24)(25)(26)(27)(28). We found that unique autoantibody signatures characterize RRMS, SPMS and PPMS based on reactivity to CNS antigens and HSP.…”
Section: Discussionmentioning
confidence: 83%
“…In the CSF, antigen microarrays in MS have detected antibodies to lipid (6) and ␣B-crystallin (23) and of note, the ␣B-crystallin reactive antibodies were of low affinity, detectable at 1:20 dilution (23). High-affinity autoreactive antibodies in the serum have not been consistently found in MS (24)(25)(26)(27)(28). We found that unique autoantibody signatures characterize RRMS, SPMS and PPMS based on reactivity to CNS antigens and HSP.…”
Section: Discussionmentioning
confidence: 83%
“…New methods have therefore been developed that enable specific detection of antibodies to properly folded and glycosylated MOG protein. The first method involves labeling of MOG transfectants with serum or CSF antibodies Lalive et al, 2006;O'Connor et al, 2007;Zhou et al, 2006), but the frequency of anti-MOG in MS still varies considerably between these studies, suggesting heterogeneity in the studied patient populations. The second method is a sensitive radioimmunoassay with a tetrameric version of folded and glycosylated MOG protein.…”
Section: Autoantibody Production By B Cellsmentioning
confidence: 99%
“…[14][15][16][17][18] In contrast, the clinical relevance of MOG antibodies in adults is unclear, as only a minority of patients with MS and NMO/NMOSD are seropositive. 16,[18][19][20][21][22][23][24] Herein, we provide evidence that MOG antibodies are a clinical biomarker of bilateral and/ or recurrent optic neuritis (BON) in adults and describe the characteristic clinical course, response to therapy, and visual outcomes of this condition.…”
mentioning
confidence: 99%